Dual-band complex-amplitude metasurface empowered high security cryptography with ultra-massive encodable patterns - Gu Zhen; Xie Rensheng; Liu Haoyang; Liu Yiting; Wang Xiong; Zhang Hualiang; Gao Jianjun; Si Liming; Chen Shuqi; Ding Jun (Nanophotonics, 2024)
The significance of a cryptograph method lies in its ability to provide high fidelity, high security, and large capacity. The emergence of metasurface-empowered cryptography offers a promising alternative due to its unparalleled wavefront modulation capabilities and easy integration with traditional schemes. However, the majority of reported strategies suffer from limited capacity as a result of restricted independent information channels. In this study, we present a novel method of cryptography that utilizes a dual-band complex-amplitude meta-hologram. The method allows for the encoding of 225 different patterns by combining a modified visual secret-sharing scheme (VSS) and a one-time-pad private key. The use of complex-amplitude modulation and the modified VSS enhances the quality and fidelity of the decrypted results. Moreover, the transmission of the private key through a separate mechanism can greatly heighten the security, and different patterns can be generated simply by altering the private key. To demonstrate the feasibility of our approach, we design, fabricate, and characterize a meta-hologram prototype. The measured results are in good agreement with the numerical ones and the design objectives. Our proposed strategy offers high security, ultra-capacity, and high fidelity, making it highly promising for applications in information encryption and anti-counterfeiting.